A comparative study of performance and emission characteristics of a diesel engine using various non-edible extracts. (17th September 2020) - Rajkumar, R.; Kannan, K. Gopi; Mohanraj, M.
In this study, the performance and emission characteristics of a diesel engine fuelled with biodiesel such as cottonseed oil, castor oil, Calophyllum inophyllum oil and mustard oil by transesterification are investigated. All biodiesels are mixed together on mass basis and allowed to transesterification is named as totally mixed esterified (TMEx). Separately transesterified and mixed together on mass basis becomes separately esterified mixer (SEMx). The biodiesel samples are prepared by a volume proportions such as 10% (SEMx10, TMEx10) and 20% (SEMx20, TMEx 20). The experiment is conducted on a single-cylinder, water-cooled, direct injection diesel engine loaded by eddy current dynamometer at different loads. Result shows that brake thermal efficiency and specific fuel consumption of TMEx blends are closer to diesel compared with SEMx blends. Also, the emission characteristics of TMEx20 are less in comparison with other blends and it is suggested as a promising replacement for diesel without engine modification.